Application of the Problem Based Learning (PBL) Model to Improve Pancasila Learning on the Behavioral Attitudes of Grade V Students in the Independent Curriculum - Pane, Siti Karlina Br Sitorus; Safrudin, Safrudin (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improve the attitudes and behavior of fifth grade students through the application of the Problem Based Learning model in learning Pancasila in the Merdeka Curriculum. The main problem faced is the lack of active participation of students and the low internalization of Pancasila values in everyday life. This research was conducted in two cycles, each of which consisted of planning, action implementation, observation, and reflection stages. The model used was project-based learning and group discussion. Data obtained through observation, interviews, and documentation. The results showed a significant increase in student attitudes and behaviors, such as a sense of responsibility, tolerance, and cooperation, after the implementation of the Problem Based Learning model. In addition, students' involvement in the learning process increased significantly. The conclusion of this study is that the application of the Problem Based Learning model is proven to be effective in improving the quality of Pancasila learning and shaping student character according to the values promoted in the Merdeka Curriculum.